PELATIHAN DIGITAL MARKETING GUNA MENINGKATKAN PANGSA PASAR PADA UMKM KEDUNGDORO KOTA SURABAYA - Athaya Illahi, Aisyah Ghina; Anggia Ayu Tambunan, Raphita Celyna; Rahmadanti , Nadya Novelia; Tharisa, Shindy Putri; Siskawati, Siskawati; Wardani, Rifda; Mar’ie Haqiqi, Syafrizal; Haratua Sinaga, Simon Fridolin; Kusuma Agung, Airlangga; Widianto, David; Puspa Arum, Dewi (CV. Era Digital Nusantara, 2022)
Indonesia is one of the countries that has been affected by the COVID-19 outbreak since early March 2020 until now. The spread of the COVID-19 outbreak has caused an unfavorable impact on various sectors. Business owners admit that there have been a lot of declines in income during this pandemic and the marketing method is only done through word of mouth, the next problem is that limited land is a trigger for MSME actors to do product marketing. In addition, 70% of MSME actors surveyed are 40-70 years old, so they do not understand how to take advantage of the sophistication of existing digitalization technology even though they already have adequate communication tools. The implementation method used in Kedungdoro Surabaya Village is training in the form of a digital marketing workshop which will be given in the form of direct practice by utilizing Google My Business social media as the media used. The results of the digitalization training activity to increase market share in the Kedungdoro sub-district generally show that this training can increase people's knowledge and understanding of the importance of utilizing digital technology to expand their product marketing.